2018
DOI: 10.1063/1.5036637
|View full text |Cite
|
Sign up to set email alerts
|

Invited Article: Molecular biomarkers characterization for human brain glioma grading using visible resonance Raman spectroscopy

Abstract: The accurate identification of the human brain tumor boundary and the complete resection of the tumor are two essential factors for the removal of the glioma tumor in brain surgery. We present a visible resonance Raman (VRR) spectroscopy technique for differentiating the brain tumor margin and glioma grading. Eighty-seven VRR spectra from twenty-one human brain specimens of four types of brain tissues, including the control, glioma grade II, III, and IV tissues, were observed. This study focuses on observing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…In addition to tryptophan, we consider that the Raman mode of 1588 cm −1 may be contributed by mitochondria, hemeproteins, and DNA bases (Supplemental Table S1). [71][72][73] Based on our previous experimental data using VRR method and autofluorescence method (to be published) on human glioma tumors 23,26,42,43,74 and the experimental and theoretical studies reported in the literature, 47,[67][68][69][70]75 we propose tryptophan as the main contributor to the Raman mode of 1588 cm −1 . One possible form of the tryptophan contribution to 1588 cm −1 mode may be tryptophan radicals because of the microenvironment in the malignant tumor tissues.…”
Section: Identification Of Glioma Grades By Tryptophanmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition to tryptophan, we consider that the Raman mode of 1588 cm −1 may be contributed by mitochondria, hemeproteins, and DNA bases (Supplemental Table S1). [71][72][73] Based on our previous experimental data using VRR method and autofluorescence method (to be published) on human glioma tumors 23,26,42,43,74 and the experimental and theoretical studies reported in the literature, 47,[67][68][69][70]75 we propose tryptophan as the main contributor to the Raman mode of 1588 cm −1 . One possible form of the tryptophan contribution to 1588 cm −1 mode may be tryptophan radicals because of the microenvironment in the malignant tumor tissues.…”
Section: Identification Of Glioma Grades By Tryptophanmentioning
confidence: 93%
“…41 It is also a new progress in molecular histopathological diagnosis and grade classification of human brain glioma tissues. 34,42 The VRR technique has been used to study human brain, breast, GYN, GI, and skin and has been used to detect vulnerable atherosclerotic plaques and to study atherosclerotic abdominal aortic tissues, cerebrospinal fluids, and breast cells since 2011. 23,26,34,42,43 The objective of this study is to use VRR as a new Raman technique to evaluate the biomarkers for glioma margins and the correlation between the levels of biomarkers and tumor grades.…”
Section: Introductionmentioning
confidence: 99%
“…VRR provides an e®ective way to enhance Raman signal from particular chemical bonds associated with key molecules and detect their changes at a molecular level, such as carotenoids, tryptophan, amides, lipids and protein in breast, skin, heart, gynecologic and brain lesions. 14,15,17 These advantages of VRR have led to a rapid progress in its applications in brain and other human cancer diagnosis 14,[17][18][19][20][21] that are di±cult to achieve by conventional nonresonance Raman method. [22][23][24][25][26][27] Recently, another new optical spatial frequency spectroscopy analysis (SFSA) method was introduced based on Fourier spatial frequency spectrum analysis of the underlying structure pattern of tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the fingerprint and high‐wavenumber regions (FP/HW) in the GA‐PLS‐LDA algorithm had an accuracy, sensitivity, and specificity of 96.76, 87.78, and 100%, respectively—higher than the analogous blood test which may be attributable to the simultaneous unique advantages of both FP and HW Raman tissue spectra (Žuvela et al, 2019). Recent work successfully used resonance Raman techniques (RRS) for brain tumor biopsies (Zhou et al, 2018, 2019), skin cancer detections (Liu et al, 2019), and breast cancer subtype separation (Bendau et al, 2020). Using spontaneous RS to scan colon cells from patients, a k‐means clustered image‐trained support vector machine was able to diagnose the samples as having Ulcerative Colitis, Crohn's disease, or no irritable bowel disease (IBD).…”
Section: Modality Of Raman Imaging On Tissuesmentioning
confidence: 99%